Literature Review Of The Role Of Strategic Management Accounting Through Mitigation Measures Against Ransomware Attacks - Yuni Astuti; Daniel Nugroho; Yanuar Ramadhan (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
The massive wave of digital transformation has increased organizational exposure to cybersecurity threats, particularly ransomware, which poses significant financial impacts. Ransomware is no longer merely a technical issue but a strategic challenge requiring a multidisciplinary mitigation approach. This study aims to examine the role of strategic management accounting in supporting mitigation efforts against ransomware attacks through a systematic literature review (SLR). The method applied is an SLR of 20 Sinta-indexed journals (levels 1–4) published between 2020 and 2024. The study was conducted from January to March 2025. The analysis reveals that strategic management accounting contributes through the integration of monitoring technologies, the development of risk governance frameworks, strengthening of organizational security culture, and optimization of security systems. Strategic management accounting also supports data-driven decision-making regarding resource allocation and security investment evaluation. This study suggests the need for synergy between accounting and information technology professionals to enhance organizational resilience. The findings offer both theoretical and practical contributions for developing more integrated and adaptive cybersecurity strategies in the face of evolving ransomware threats.